Cross-cultural adaptation of the Portuguese version of the patient-generated subjective global assessment - Duarte Bonini Campos, J. A. [UNESP]; Dias do Prado, C. [UNESP] (Aula Médica Ediciones, 2012)
Introduction: The cross-cultural adaptation of the Patient-Generated Subjective Global Assessment is important so it can be used with confidence in Portuguese language.Objective: To perform a cross-cultural adaptation of the Portuguese version of the Patient-Generated Subjective Global Assessment and to estimate its intrarater reliability.Material and methods: This is a validation study. Face Validity was classified by 17 health professionals and 10 Portuguese language specialists. Idiomatic, semantic, cultural and conceptual equivalences were analyzed. The questionnaire was completed by 20 patients of the Amaral Carvalho Hospital (Jau, São Paulo, Brazil) in order to verify the Comprehension Index of each item. Therefore, 27 committee members classified each item into "essential", "useful, but not essential" and "not necessary", in order to calculate the Content Validity Ratio. After, this version of the questionnaire was applied twice to 62 patients of the hospital cited above. The intrarater reliability of the nutritional status analyzed by Patient-Generated Subjective Global Assessment was estimated by Kappa statistics.Results: The Portuguese version of the Patient-Generated Subjective Global Assessment presented 10 incomprehensible expressions. The items "a year ago weight" and "dry mouth symptom" presented the lowest Content Validity Ratio. Substantial intrarater reliability (k = 0.78, p = 0.001) was observed.Conclusion: The cross-cultural adaptation of the Portuguese version of the Patient-Generated Subjective Global Assessment became simple and understandable for Brazilian patients. Thus, this version of the Patient-Generated Subjective Global Assessment was considered a valid and a reliable method. (Nutr Hosp. 2012;27:583-589) DOI:10.3305/nh.2012.27.2.5634
Keywords: Neoplasms; Nutritional status; Cachexia Validation studies; Psychometrics